Bring the pain: wounding reveals a transition from cortical excitability to epithelial excitability in Xenopus embryos - Sepaniac, Leslie A.; Davenport, Nicholas R.; Bement, William M. (Frontiers in Cell and Developmental Biology, 2024)
The cell cortex plays many critical roles, including interpreting and responding to internal and external signals. One behavior which supports a cell's ability to respond to both external and internally-derived signaling is cortical excitability, wherein coupled positive and negative feedback loops generate waves of actin polymerization and depolymerization at the cortex. Cortical excitability is a highly conserved behavior, having been demonstrated in many cell types and organisms. One system wellsuited to studying cortical excitability is Xenopus laevis, in which cortical excitability is easily monitored for many hours after fertilization. Indeed, recent investigations using X. laevis have furthered our understanding of the circuitry underlying cortical excitability and how it contributes to cytokinesis. Here, we describe the impact of wounding, which represents both a chemical and a physical signal, to cortical excitability. In early embryos (zygotes to early blastulae), we find that wounding results in a transient cessation of wave propagation followed by transport of waves toward the wound site. We also find that wounding near cell-cell junctions results in the formation of an actin based structure that pulls the junction toward the wound. In later embryos (late blastulae to gastrulae), we find that as cortical excitability diminishes it is replaced by epithelial excitability, a process in which wounded cells communicate with other cells via a wave-like increase of calcium and apical F-actin. Thus, as cortical excitability is disappearing from the individual, cellular level within the embryo, excitability is emerging instead at the level of the embryonic epithelium itself.